TOURISM INDUSTRY AND ECONOMIC PROGRESS IN JAMMU AND KASHMIR: A DEVELOPMENT PERSPECTIVE - Dr. Shabir Ahmad Lone; Dr. E. Ravi; Dr. Javad Ahmad Mir (RADJA PUBLIKA, 2026)
Tourism is widely acknowledged as one of the most rapidly expanding sectors in the global economy, generating substantial economic and social benefits. In the case of Jammu and Kashmir, often referred to as the “Paradise on Earth” and the “Switzerland of the Indies,” tourism plays a crucial role in the economic structure of the region. The sector significantly contributes to employment generation, infrastructure development, revenue creation, and the promotion of balanced regional as well as rural development. This study aims to provide a comprehensive evaluation of the contribution of tourism to the economy of Jammu and Kashmir. The analysis is based exclusively on secondary data obtained from various published reports, books, and research studies. The findings indicate that although the tourism industry serves as an important driver of economic and social progress in the region, its overall potential has not yet been fully realized. Furthermore, the study identifies a notable gender disparity within the sector, as tourism-related employment remains largely male-dominated with limited participation of women. It highlights the necessity for effective government policies and greater involvement of local communities to promote inclusive and sustainable tourism development.